1983
DOI: 10.1103/physreva.28.2408
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of structural transitions in liquids

Abstract: The "inherent structures" which underlie the liquid state are those stable particle packings (potential minima) which can be reached by a steepest-descent quench on the potential-energy hypersurface. This paper explores the dynamics of transition between distinct inherent structures for a simple classical model of monatomic substances. Molecular-dynamics calculations with 32 and 108 particles have been carried out with running construction of the mapping to potential minima. This determines the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
339
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 596 publications
(343 citation statements)
references
References 7 publications
3
339
0
1
Order By: Relevance
“…That is, rather than simply modifying the way in which potential energy information is processed, we seek to distort the potential in such a way that we obtain an algorithmic advantage while leaving the global minimum essentially intact. Early work by Stillinger and Stillinger 23 is an example of this type of approach. They sought to reduce the number of local minima by altering the long-range form of simple pair potentials.…”
Section: Formal Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, rather than simply modifying the way in which potential energy information is processed, we seek to distort the potential in such a way that we obtain an algorithmic advantage while leaving the global minimum essentially intact. Early work by Stillinger and Stillinger 23 is an example of this type of approach. They sought to reduce the number of local minima by altering the long-range form of simple pair potentials.…”
Section: Formal Developmentsmentioning
confidence: 99%
“…Strategies based on "smoothing" techniques have also been proposed. 18,23 More recently, Wales et al 10,27 have devised an approach based on a "basin hopping" methodology in which the original potential energy at each point is replaced by the energy of its corresponding local minimum or "inherent structure". 22,24,25 By construction, the basin hopping method, unlike some distortion strategies, is guaranteed to leave the energetics of the various potential minima unaltered.…”
Section: Formal Developmentsmentioning
confidence: 99%
“…Given a unique configurational mapping process, it can be rigorously shown that the thermodynamics of glasses and supercooled liquids can be described in terms of the distribution of inherent structure energies; 39 at the same time, dynamics are related to transitions between basins. 59 Within the energetic hierarchy of this formalism, it naturally follows that crystalline solids are systems occupying the lowest-lying energy basins; glasses are systems trapped within amorphous inherent structures whose energies are higher than that of the crystal; and deeply supercooled liquids are systems that move infrequently between amorphous basins.…”
Section: Energy Landscape/inherent Structure Formalismmentioning
confidence: 99%
“…In another (i.e. dynamic n-tuple computation), n-tuple lists within given interaction ranges are constructed at every simulation time step [3,4]. Recent advancements in chemically reactive MD simulations [5] have renewed interests in efficient implementation of dynamic n-tuple computation [6].…”
Section: Introductionmentioning
confidence: 99%